Strategies of Agriculture Practices for Transformation and Empowerment of The Rural Economy - Dr. Pallavi Kumari (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Agricultural practices performed by the potential farmers largely impact the development of any economy. Agriculture is an important sector of the Indian economy as it contributes about 17% to the total GDP and provides employment to over 60% of the population. If we want the industrial sector to grow in tremendous scale, the agriculture growth needs to be boosted. The government has been launching various schemes and credit facilities for the farmers so the agricultural productivity may be increased. This paper will attempt to discuss the various issues and challenges which are impacting the agricultural growth. Agriculture has been providing support for human survival and supporting the sustainability objectives. It not only ensure food security for the present population but also ensure the generation of employment opportunities. During the last 6 years ending 2017-18, the Food Processing Industries sector has been growing at an Average Annual Growth Rate (AAGR) of around 5.06 per cent. The sector constituted as much as 8.83 per cent and 10.66 per cent of GVA in Manufacturing and Agriculture sector respectively in 2017-18 at 2011-12 prices. It has been apparent that there has been a large imbalance in demand and supply of the food supply due to increasing population, a change in people’s living standards, economic growth and changing climatic conditions. In spite of the technological advancement, the technology is still not reached the rural farmers and hence there is a need to overcome the huddles which come across the agricultural productivity i.e heavy shortages of water and cultivated land, low productivity, inefficient irrigation or agricultural planning and management. This paper will discuss how the uneven distribution can be channelized and various steps could be taken as a remedial measure for solving the issue which in turn increases productivity to support the livelihood of the rural population. The aim of development in agriculture should also go a long way in supporting the program of generating jobs for the unemployed and bringing high standard of living, economic prosperity and agricultural sustainability.